Effects of Different Plasticizers on the Structure, Physical Properties and Film Forming Performance of Curdlan Edible Films - Ying Chen; Jing Wang; Liang Xu; Yuping Nie; Yunyue Ye; Jianya Qian; Fengsong Liu; Liang Zhang (Foods)
This study successfully developed edible films with excellent mechanical strength and notable water resistance, utilizing curdlan (CL) as the primary matrix and incorporating various plasticizers, including glycerol (GLY), ethylene glycol (EG), propylene glycol (PRO), xylitol (XY), sorbitol (SOR), and polyethylene glycol (PEG). A comprehensive suite of analytical techniques, including Fourier transform infrared spectroscopy (FTIR), wide-angle X-ray diffraction (XRD), scanning electron microscopy (SEM), dynamic mechanical analysis (DMA), and tensile testing, were employed to evaluate the films’ structural and mechanical properties. After incorporating PEG, the water sensitivity increased slightly, with a contact angle (CA) of 97.6°, and a water solubility (WS) of 18.75%. The inclusion of plasticizers altered the crystalline structure of the CL matrix, smoothing and flattening the film surface while reducing hydrogen-bonding interactions. These structural changes led to a more uniform distribution of amorphous chain segments and a decrease in glass transition temperatures. Among the tested plasticizers, GLY exhibited the highest compatibility with CL, resulting in the smoothest surface morphology and delivering the most effective plasticizing effect. The CL-GLY film showed a dramatic improvement in flexibility, with an elongation at break that was 5.2 times higher than that of the unplasticized film (increasing from 5.39% to 33.14%), indicating significant enhancement in extensibility. Overall, these findings highlight the potential of CL-GLY films as sustainable and effective materials for food packaging applications.